2019
DOI: 10.3759/tropics.ms18-13
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between leaf flushing phenology and defensive traits of canopy trees of five dipterocarp species in a tropical rain forest

Abstract: While the canopy layer shows the highest productivity in forests, it also has the highest herbivore population density. How do canopy trees cope with attack from herbivores under such conditions? We investigated the relationship between leaf flushing phenology, defensive and photosynthetic traits, such as leaf flushing frequency, the number of emerging leaves per flushing term, the leaf life span, total phenolic and condensed tannin contents, leaf toughness, leaf nitrogen content, the photosynthetic rate at li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
(80 reference statements)
1
4
0
Order By: Relevance
“…Leaves with a high LMA, i.e., thick leaves, typically have a well-developed palisade layer, which has high photosynthetic capability (Koike 1988(Koike , 2001Kenzo et al 2004Kenzo et al , 2006. A similar correlation has been reported in many other plant species, including some tropical trees (Reich et al 1991;Wright et al 2004;Kenzo et al 2012Kenzo et al , 2015Yoneyama and Ichie 2019). The increased LMA under the open control observed in this study may also have contributed to increased drought tolerance (Kramer 1983;Niinemets 2001).…”
Section: Ecophysiological Traits and Seedling Growthsupporting
confidence: 82%
“…Leaves with a high LMA, i.e., thick leaves, typically have a well-developed palisade layer, which has high photosynthetic capability (Koike 1988(Koike , 2001Kenzo et al 2004Kenzo et al , 2006. A similar correlation has been reported in many other plant species, including some tropical trees (Reich et al 1991;Wright et al 2004;Kenzo et al 2012Kenzo et al , 2015Yoneyama and Ichie 2019). The increased LMA under the open control observed in this study may also have contributed to increased drought tolerance (Kramer 1983;Niinemets 2001).…”
Section: Ecophysiological Traits and Seedling Growthsupporting
confidence: 82%
“…We found leaf number within a sampling unit was similar between seasons, suggesting that the changes in total leaf number did not drive the changes in herbivore abundance with the season. On the other hand, during the dry season when new leaves flush (Zheng et al, 2001), more high‐quality (nutritious and less toxic) young leaves become available to herbivores, facilitating herbivores that are otherwise sensitive and limited by plant chemical defences (Yoneyama & Ichie, 2019), increasing bottom‐up effects. Although most of the herbivores in the dry season were oligophagous specialists, these species could still be sensitive to chemical defence and nutrition and are more likely to be flush feeders (Cates, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have associated the variation in leaf lifespan with the ecological group in which a species is included and the herbivory rate (Coley 1988; Poorter et al 2004; Lusk et al 2008; Cardenas et al 2014). In tropical rainforests, even non‐pioneer species in the same family may have different leaf lifespans (Yoneyama & Ichie 2019). Thus, for species with unknown leaf dynamics, a herbivory indicator measured at a single moment in time (herbivore damage) should be used with caution as a predictor of the actual damage experienced by a species (Poorter et al 2004; Andrew et al 2012; Zhang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest the presence of a negative association due to the light environment in which species grow (Baraza et al 2004; Chacon & Armesto 2006; Glassmire et al 2019), while others have reported a positive correlation between secondary compounds (mainly phenolic compounds) and the herbivory amount (Silva et al 2015), attributing this relationship to the successional stage (Poorter et al 2004; Silva et al 2012). In addition, the association between herbivory and chemical compounds can also be related to the leaf life span and leaf dynamics of the species (Coley 1988; Yoneyama & Ichie 2019).…”
Section: Introductionmentioning
confidence: 99%